RANCANG BANGUN ALAT PELATIHAN PARKIR MOBIL BERBASIS MIKROKONTROLER - Adnediel, Gery; Yendri, Dodon (CHIPSET, 2024)
The increasingly limited parking area certainly requires someone to be more proficient in parking a car. Arduino is an electronic board device equipped with open source software, where this device is included in the ATMega microcontroller family and functions as a single-board microcontroller designed to facilitate the use of electronics in various fields released by Atmel. The ultrasonic sensor HC-SR04 is an ultrasonic sensor that works like a sonar system on Bats and Dolphins where in this sensor there is a sender and receiver, this sensor has a range specification of 2 cm - 400 cm with a resolution of 0.3 cm, and an angle range of less than 15 degrees. To prevent failure or mistakes when parking a car usually takes longer to learn than learning to drive a car itself. LCD (Liquid Crystal Display) functions as a display medium that uses liquid crystals as a display of data, characters, letters and graphics.